1988
DOI: 10.1111/j.1365-2494.1988.tb02153.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sowing date, placement of seed, vegetation suppression, slugs, and insects upon establishment of no‐till alfalfa in orchardgrass sod†

Abstract: Four treatments designed to affect some environmental factors during germination and establishment of alfalfa were: two sowing dates (March and May) to produce differences in temperature, light and soil moisture; two sowing methods (notill drill and hand sowing) for creating different degrees of soil-seed contact; mowing and banded and broadcast sprays of glyphosate to produce varying degrees of plant competition; and methiocarb bait combined with carbofuran granules vs. no pesticide to establish different lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
(24 reference statements)
0
10
0
Order By: Relevance
“…Pest and disease problems at establishment. Predation by a range of insect (15,74,98) or mollusk (5,15,33,57,93,98) pests may result in less effective establishment and reduced yield of newly-sown forages. This damage may be more acute in crops sown by minimal tillage than with conventional cultivation (33,57,74,94), however, Ellis et al (36) noted that the incidence of damage by frit fly (Oscinella frit L.) was greater in conventional than in no-till seedings, and attributed this to a dilution of predator effect over both resident and establishing plants.…”
Section: Effects Of Minimal-tillage Practices On Pasture Plant Emergencementioning
confidence: 99%
See 1 more Smart Citation
“…Pest and disease problems at establishment. Predation by a range of insect (15,74,98) or mollusk (5,15,33,57,93,98) pests may result in less effective establishment and reduced yield of newly-sown forages. This damage may be more acute in crops sown by minimal tillage than with conventional cultivation (33,57,74,94), however, Ellis et al (36) noted that the incidence of damage by frit fly (Oscinella frit L.) was greater in conventional than in no-till seedings, and attributed this to a dilution of predator effect over both resident and establishing plants.…”
Section: Effects Of Minimal-tillage Practices On Pasture Plant Emergencementioning
confidence: 99%
“…The effectiveness of pesticide or fungicide in improving yield is variable, and depends on the extent of pest or disease challenge to the crop (5,54,97). Modification of planting dates to avoid periods of high pest population may be more effective than pesticide application in reducing the effects of predators (15,54,74).…”
Section: Effects Of Minimal-tillage Practices On Pasture Plant Emergencementioning
confidence: 99%
“…For example, Rioux (1994) reported that compared with broadcasting, banding of herbicide increased renovation year total forage yields and reduced weed content. In contrast, Byers and Templeton (1988) reported that herbicide banding reduced total forage, sod-seeded legumes, digestible dry matter, and crude protein (CP) yields. Thus, even with good management, use of herbicide as a sod suppression method can result in undesirable swards.…”
mentioning
confidence: 98%
“…Because of slugs, Deroceras reticulatum (Muller), D. laeve (Muller) and Arion fasciatus (Nilsson), attempts to establish luceme by conservation tillage methods often fail, especially in grass sods (Grant et al, 1982;Byers etal., 1985: Byers andTempleton, 1988). Because of slugs, Deroceras reticulatum (Muller), D. laeve (Muller) and Arion fasciatus (Nilsson), attempts to establish luceme by conservation tillage methods often fail, especially in grass sods (Grant et al, 1982;Byers etal., 1985: Byers andTempleton, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Grass sods and crop residues provide excellent habitats for invertebrates. Because of slugs, Deroceras reticulatum (Muller), D. laeve (Muller) and Arion fasciatus (Nilsson), attempts to establish luceme by conservation tillage methods often fail, especially in grass sods (Grant et al, 1982;Byers etal., 1985: Byers andTempleton, 1988). Slugs are also a problem in establishing luceme into luceme (Byers and Bierlein, 1984), wheat (Triticum ae.itivum L.) (Dowling and Linscott, 1983) and oat residues (Stout et al, 1992).…”
Section: Introductionmentioning
confidence: 99%